1998
DOI: 10.1111/j.1600-0447.1998.tb05960.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity as a fundamental feature of generalized anxiety disorders: results from the National Comorbidity Study (NCS)

Abstract: Generalized anxiety disorder (GAD) is a relatively commun mental disorder in the general population, afflicting approximately 3% of community residents during their lifetime. It is not a benign condition, since significantly increased disability and dysfunction are found in GAD subjects compared to non‐GAD subjects. For decades GAD has frequently been observed in the context of other mental and substance abuse disorders. Initially the weight of clinical opinion indicated that GAD was a residual disease which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 11 publications
7
114
2
7
Order By: Relevance
“…A study of past-year DSM-III-R disorders showed that 27% of respondents with comorbid GAD/MDD (n 5 99) reported the highest level of social impairment on a measure of social functioning compared with 8.4% of respondents with neither disorder (n 5 5217); the corresponding proportion was 24% and 23% for respondents with pure GAD (n 5 92) and pure MDD (n 5 489), respectively . A similar pattern was observed for respondents with lifetime GAD when comorbidity with other affective disorders was examined [Judd et al, 1998]. …”
Section: General Population Studies Examining Role And/or Qol Impairmmentioning
confidence: 55%
“…A study of past-year DSM-III-R disorders showed that 27% of respondents with comorbid GAD/MDD (n 5 99) reported the highest level of social impairment on a measure of social functioning compared with 8.4% of respondents with neither disorder (n 5 5217); the corresponding proportion was 24% and 23% for respondents with pure GAD (n 5 92) and pure MDD (n 5 489), respectively . A similar pattern was observed for respondents with lifetime GAD when comorbidity with other affective disorders was examined [Judd et al, 1998]. …”
Section: General Population Studies Examining Role And/or Qol Impairmmentioning
confidence: 55%
“…De acordo com o DSM-5, para ser diagnosticada, deve durar pelo menos seis meses e ser acompanhada de pelo menos três dos seguintes sintomas: inquietação, irritabilidade, fatigabilidade, perturbação do sono, tensão muscular e/ ou dificuldade de concentração 2 . O National Comorbidity Survey Replication (NCS-R), principal estudo epidemiológico norte-americano, que avaliou 9.282 pessoas da comunidade, encontrou prevalência de 5,7% de TAG durante a vida 3 , enquanto estudos europeus chegaram a relatar prevalência de até 6,9% 4 . O Estudo Epidemiológico dos Transtornos Mentais São Paulo Megacity (2009), que avaliou 5.037 indivíduos da região metropolitana de São Paulo, revelou que 19,9% apresentam algum transtorno de ansiedade e 2,3% possuem TAG 5 ; essas proporções, segundo esse mesmo estudo, seriam semelhantes às encontradas em outros grandes centros urbanos brasileiros.…”
Section: Introductionunclassified
“…The principal data on comorbidity of affective and anxiety disorders are listed in the table 1. This table has been created based on literature findings relevant to prevalence of depression and anxiety and their concomitant existence in general population Kessler, 1999;Kessler et al, 1994Kessler et al, , 1995Kessler et al, , 1996Kessler et al, , 1999Judd et al, 1998 As can be seen from table 1 there are certain discrepancies in variables "Comorbidity 1" and "Comorbidity 2": the "Comorbidity 1" is 2 -5,5 fold lower, then "Comorbidity 2" level. In other words, the primary and main diagnosis of MDD has caused lower level of comorbidity with any AD, while the primary diagnosis of AD has lead to higher level of comorbidity with MDD, and the last category seems to be more consistently present in comorbid pairs, than AD.…”
Section: The Prevalence Of Affective and Anxiety Disorders And Asymmementioning
confidence: 99%